Peran Guru PAI Mengatasi Bullying SD 045/XI Koto Dua Kota Sungai Penuh - Muhammad Habil; Nurfarida Deliani; Juliana Batubara (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
. The purpose of this research is to find out the role of PAI teachers in overcoming bullying at SD 045/XI Koto Dua. Bullying is a serious problem that often occurs in the school environment which can affect the development of students both emotionally and socially. Bullying behavior can also have a negative impact, either for the victim or the perpetrator himself. If this happens in elementary school, the role of a PAI teacher is needed in order to deal with this behavior. Qualitative research approach and descriptive method, which is research that describes the conditions that are happening, using data collection techniques used are interview, observation, and documentation methods. The results of this study indicate that the role of PAI teachers in overcoming bullying behavior by giving advice to students who are bullying so as not to do it again if it happens again it will be dealt with more harshly. Furthermore, calling the parents of the bullying perpetrators to inform their parents about what students do at school. PAI teachers must have methods in overcoming bullying. How to overcome bullying in Sd tersebu give advice about religion either individually or as a whole students give an understanding of bullying and its impact especially to students. For this reason, PAI teachers play a very important role in overcoming bullying behavior to students so that this behavior does not continue into adolescence.